2021
DOI: 10.1080/21655979.2021.1974805
|View full text |Cite|
|
Sign up to set email alerts
|

Circular RNA CNOT2 knockdown regulates twist family BHLH transcription factor via targeting microRNA 409-3p to prevent breast cancer invasion, migration and epithelial–mesenchymal transition

Abstract: Numerous studies have manifested that cicular RNA (circRNA) is closely associated with the development of breast cancer (BC), but the specific mechanism has not been fully clarified. The purpose of this study was to investigate the effect of circCNOT2 on BC invasion, migration and epithelial mesenchymal transition (EMT) and its potential molecular mechanism. The results assured that circCNOT2 and Twist Family BHLH Transcription Factor (TWIST1) were elevated in BC, while microrNA (miR)-409-3p was reduced. CircC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…MiR-409-3p not only exists in tissues and cells but also stably exists in circulating body fluids. For the most part, miR-409-3p acts as a tumor suppressor and was reported to be downregulated in a minimum of 13 cancers, including NSCLC ( 12 , 14 - 17 , 19 - 21 ), BC ( 24 , 26 , 27 , 29 , 30 ), CC ( 31 - 35 ), osteosarcoma ( 36 - 39 ), GC ( 40 - 44 ), CRC ( 45 , 46 , 48 - 51 ), OC ( 53 - 55 ), ccRCC ( 57 , 58 ), BCa ( 59 , 61 ), PTC ( 62 ), AML ( 65 , 66 ), oligodendrogliomas ( 67 ), melanoma ( 68 ), TSCC ( 70 ), glioma ( 79 ), fibrosarcoma ( 81 ) and HCC ( 83 , 84 ). However, miR-409-3p also serves as an oncogene to promote tumor progression.…”
Section: Aberrant Expression Of Mir-409-3p In Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-409-3p not only exists in tissues and cells but also stably exists in circulating body fluids. For the most part, miR-409-3p acts as a tumor suppressor and was reported to be downregulated in a minimum of 13 cancers, including NSCLC ( 12 , 14 - 17 , 19 - 21 ), BC ( 24 , 26 , 27 , 29 , 30 ), CC ( 31 - 35 ), osteosarcoma ( 36 - 39 ), GC ( 40 - 44 ), CRC ( 45 , 46 , 48 - 51 ), OC ( 53 - 55 ), ccRCC ( 57 , 58 ), BCa ( 59 , 61 ), PTC ( 62 ), AML ( 65 , 66 ), oligodendrogliomas ( 67 ), melanoma ( 68 ), TSCC ( 70 ), glioma ( 79 ), fibrosarcoma ( 81 ) and HCC ( 83 , 84 ). However, miR-409-3p also serves as an oncogene to promote tumor progression.…”
Section: Aberrant Expression Of Mir-409-3p In Cancersmentioning
confidence: 99%
“…Twist family bHLH transcription factor 1 could induce EMT and participate in cancer metastasis ( 100 ). A Transwell assay performed by Su et al ( 29 ) found that miR-409-3p overexpression could limit the EMT in MCF7 BC cells. KLF17 is a member of a conserved family of transcription factors that regulates cell migration and invasion.…”
Section: Biological Roles Of Mir-409-3p In Cancers In Vitromentioning
confidence: 99%
“…For example, circ_0047303 may be a potential key regulator to mediate the upregulation of key angiogenesis-related genes, including HIF-1, EIF4E2, and VEGFA in TNBC, via sponging the tumor-suppressive miRNAs [64], circ_0000518 promotes breast cancer progression through the miRNA-1225-3p/SRY-box transcription factor 4 pathway, and it is oncogenic in BC [65], circ_0089153 is an oncogene in breast cancer, which enhances proliferation and metastasis via sponging miR-2467-3p/E2F6 [66], circ_IRAK3 exerts a promoting effect on BC progression by modulating the miR-603/KIF2A axis [67], circRNA_000554 up-regulates ZFP36 by sponging miR-182 [68], circ_RPPH1 up-regulates ARHGAP1 via sponging miR-542-3p [69], circ_ZFR up-regulates FABP7 by sponging miR-223-3p [70]. Hsa-circ-0061825 (circ-TFF1) contributes to BC via targeting miR-326/TFF1 [71], and circ-NOT2 can prevent breast cancer invasion, migration and EMT by regulating twist family BHLH transcription factor via targeting miR-409-3p/Twist1 [72]. CircNOL10, however, can up-regulate SOCS2 and inhibit the JAK2/STAT5 pathway by sponging miR-767-5p, inhibit BC cell proliferation, migration, invasion, and EMT, and slow down the growth of xenograft tumors in vivo [73].…”
Section: Circrna-associated Cerna Network In Breast Cancermentioning
confidence: 99%
“…11 CircCNOT2 silencing facilitated apoptosis and arrested cell proliferation and motility. 12 Cir-cRNA septin 9 (circSEPT9), a member of the circRNAs family, was demonstrated to be upregulated in BC. 13 However, the mechanism of action of circSEPT9 in BC is not yet known.…”
Section: Introductionmentioning
confidence: 99%
“…For example, knockdown of circ_0068631 remarkably retarded the proliferation and migration of BC cells 11 . CircCNOT2 silencing facilitated apoptosis and arrested cell proliferation and motility 12 . CircRNA septin 9 (circSEPT9), a member of the circRNAs family, was demonstrated to be upregulated in BC 13 .…”
Section: Introductionmentioning
confidence: 99%